2007
DOI: 10.1002/chem.200601209
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogen Peroxide Decomposition by a Non‐Heme Iron(III) Catalase Mimic: A DFT Study

Abstract: Non-heme iron(III) complexes of 14-membered tetraaza macrocycles have previously been found to catalytically decompose hydrogen peroxide to water and molecular oxygen, like the native enzyme catalase. Here the mechanism of this reaction is theoretically investigated by DFT calculations at the (U)B3LYP/6-31G* level, with focus on the reactivity of the possible spin states of the FeIII complexes. The computations suggest that H2O2 decomposition follows a homolytic route with intermediate formation of an iron(IV)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
36
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(41 citation statements)
references
References 64 publications
5
36
0
Order By: Relevance
“…The hybrid Becke-Lee-Yang-Parr (B3LYP) functional [21,22] and the 6-31 G(d) basis set were used for complete geometry optimization without any symmetry constraint. The level has been proved suitable for geometry optimization of iron porphyrins [23][24][25][26][27][28][29]. The following frequency analysis revealed that all the structures obtained in this work had no imaginary vibration, indicating that the lowest energy structures for all of the complexes were truly local minima in the potential energy surfaces.…”
Section: Methodsmentioning
confidence: 90%
“…The hybrid Becke-Lee-Yang-Parr (B3LYP) functional [21,22] and the 6-31 G(d) basis set were used for complete geometry optimization without any symmetry constraint. The level has been proved suitable for geometry optimization of iron porphyrins [23][24][25][26][27][28][29]. The following frequency analysis revealed that all the structures obtained in this work had no imaginary vibration, indicating that the lowest energy structures for all of the complexes were truly local minima in the potential energy surfaces.…”
Section: Methodsmentioning
confidence: 90%
“…Since the BP86 is known to underestimate the energy barrier for hydrogen atom transfers [37], the energy values were further refined using the hybrid B3LYP functional [38][39][40]. The B3LYP functional has been found to give accurate energies for energy barriers in the catalytic cycle of a non-heme catalase mimic [41]. To this aim, single point energy calculations were performed with the ORCA program [42] on the CPMD optimized structures of reactants and transition states using both B3LYP and BP86 and the TZVP basis set [43].…”
Section: Computational Detailsmentioning
confidence: 99%
“…64,65 The present investigation follows the reaction pathway in reference 64 . A flaw in that study is that the additional axial (proximal) ligand was not taken into account.…”
Section: Reaction Between Hydrogen Peroxide and A Non-heme Iron Camentioning
confidence: 99%
“…The reason for this electron transfer is probably the lack of the distal ligand. 65 The spin on iron couples ferromagnetically with the spin of the unpaired electron on of the ligand to form a quartet state. The present assignment agrees with the results in reference 64 (unpaired electrons in d z2 , d xz and the ligand b 1u orbitals).…”
Section: Reaction Between Hydrogen Peroxide and A Non-heme Iron Camentioning
confidence: 99%